INTERNATIONAL LAW ENFORCEMENT COOPERATION - Tryfon, Korontzis (European Scientific Journal, ESJ, 2014)
Modern states have created a society based on freedom, security and justice, respecting relevant international legal texts drawn up for this purpose, such as the European Convention on the Protection of Human Rights and on Fundamental Freedoms. The current-modern society is characterized by an elation of criminal activities and particularly of organized crime as also and of terrorism which international character, proves that for illegal activities there are no borders. Modern criminals’ businessmen trivialize and corrupt legitimate economies, societies and the state law through transnational criminal markets and by forming international illegal trade alliances. It is responsibility of all governments for their citizens’ benefit, to undertake effective measures in order to combat crime and its causes, with full respect on individuals’ fundamental rights, including personal data protection. Recognizing the important role that effective information exchange and close cooperation between the law enforcement agencies play in order to prevent and combat all forms of crime and serious crime, including terrorism, has been promoted the international law enforcement cooperation with the establishment of International and European organizations.